Recent advances in one-stage conversion of lipid-based biomass-derived oils into fuel components – aromatics and isomerized alkanes. (15th October 2020) - Yeletsky, P.M.; Kukushkin, R.G.; Yakovlev, V.A.; Chen, B.H.
Graphical abstract: Highlights: Two routes of one-stage conversion of lipidic feedstocks to aromatics and i-alkanes are reviewed. The first route is direct cracking of the feedstocks to produce aromatics. The second route is merged hydrodeoxygenation-hydroisomerization to obtain i-alkanes. Zeolite-based catalysts were shown to be the most perspective in the both approaches. Techno-economic analysis of production of lipid-derived biofuels is presented briefly. Abstract: Nowadays, production of biofuels is a rather hot topic due to depleting of conventional fossil fuel feedstocks and a number of other factors. Plant lipid-based feedstocks are very important for production of diesel-, kerosene-, and gasoline-like hydrocarbons. Usually, (hydro)deoxygenation processes are aimed at obtaining of linear hydrocarbons known to have poor fuel characteristics compared to the branched ones. Thus, further hydroisomerization is required to improve their properties as motor fuel components. This review article is focused on conversion of lipid-based feedstocks and model compounds into high-quality fuel components for a single step – direct cracking into aromatics and merged hydrodeoxygenation-hydroisomerization to obtain isoparaffins. The second process is quite novel and a number of the research articles presented in the literature is relatively low. As auxiliary subsections, hydroisomerization of straight hydrocarbons and techno-economic analysis of renewable diesel-like fuel production are briefly reviewed as well.